Penggunaan Aplikasi Audit Tool and Linked Archive System oleh Kantor Akuntan Publik - Paramita, Ni Made Wirya Sri Shinta; Ariyanto, Dodik (E-Jurnal Akuntansi; Vol 33 No 5 (2023), 2023)
The Audit Tool and Linked Archive System (ATLAS) application is a tool that assists auditors in mastering and implementing auditing standards in channeling their professional services, so it is hoped that the audit quality will increase. The aim of this study was to determine the effect of perceived convenience, perceived usefulness and auditors' trust in the use of the ATLAS application in completing their assignments. Data sourced from distributing questionnaires with a total of 45 auditors as respondents. The sample selection used purposive sampling method and was analyzed using multiple linear regression analysis techniques. The results of this study are that perceived convenience has a significant effect on ATLAS applications, perceived usefulness has no effect on ATLAS applications, and trust has a significant and positive effect on ATLAS applications. Keywords: Perceived Ease of Use; Perceived Usefulness; Trust; ATLAS Application.